Frequency and Clinical Epidemiology of Canine Monocytic Ehrlichiosis in Dogs Infested with Ticks from Sinaloa, Mexico. (24th October 2013) - Sosa-Gutierrez, Carolina Guadalupe; Quintero Martinez, Maria Teresa; Gaxiola Camacho, Soila Maribel; Cota Guajardo, Silvia; Esteve-Gassent, Maria D.; Gordillo-Pérez, María-Guadalupe
Abstract : Ehrlichia canis is a rickettsial intracellular obligate bacterial pathogen and agent of canine monocytic ehrlichiosis. The prevalence of this disease in veterinary medicine can vary depending on the diagnostic method used and the geographic location. One hundred and fifty-two canine blood samples from six veterinary clinics and two shelters from Sinaloa State (Mexico) were analyzed in this study. All animals were suspected of having Canine Monocytic Ehrlichiosis (CME). The diagnostic methods used were the ELISA (Snap4Dx, IDEXX) together with blood smear and platelet count. From all dogs blood samples analyzed, 74.3% were positive to E. canis by ELISA and 40.1% were positive by blood smear. The sensitivity and specificity observed in the ELISA test were 78.8% and 86.7%. In addition, thrombocytopenia was presented in 87.6% of positive dogs. The predominant clinical manifestations observed were fever, anorexia, depression, lethargy, and petechiae. Consequently, this is the first report in which the morulae were visualized in the blood samples, and E. canis -specific antibodies were detected in dogs from Sinaloa, Northwest of Mexico.